Overview of occupational hearing noise management in Malaysia - Ismail, Noraidah; Rahmat, Sarah (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2018)
Introduction: This paper aims to synthesize available literature on occupational noise in Malaysia and to relate this to the current noise management practices and control. The review focuses on several main scopes; i) history of occupational noise management in Malaysia; ii) legislative developments and legal precedents of occupational noise in Malaysia ; and iii) the hearing conservation programs (HCP) and hearing loss prevention programs (HLPP). Design: Narrative review and synthesis Method: Related publications and references were identified through several ways: i) by structured searches in PubMed, Google scholar, Web of Knowledge and Science Direct using the combinations of ‘occupational noise’, ‘noise induced hearing loss; ‘hearing’, ‘knowledge’, awareness’, ‘hearing conservation program’, ‘hearing protection devices’ as key words ii) by inspecting the reference lists of relevant articles. Results: The number of publications within the audiology which address this topic, is rather limited. All the above mentioned scopes were discussed and synthesis of literature from other related fields such as medical, health and occupational safety and health were also referred to facilitate the discussion. Conclusion: This paper concludes that there are an emerging trend for the studies of occupational noise Malaysia in the literature. However, the effectiveness ofHCP in Malaysia, and to what extent it is accepted and being implemented is yet to be investigated.